Portal hypertensive enteropathy: multimodality assessment through computed tomography and magnetic resonance enterography - Giuseppe Cicero, MD, PhD; Francesco Marcello Aricò, MD; Anna Viola, MD, PhD; Velio Ascenti, MD; Silvio Mazziotti, MD (Radiology Case Reports, 2022)
Portal hypertension consists in an increased portal vein pressure due to prehepatic, hepatic, or posthepatic conditions, with cirrhosis representing the most common cause. The gastrointestinal tract can be secondarily affected not only with varices formation, whose rupture is one of the most dangerous complications, but also with small and large bowel involvement which can predispose to chronic intestinal bleeding. These conditions respectively take the name of portal hypertensive enteropathy and portal colonopathy and their assessment are of almost exclusive pertinence of endoscopic techniques. Up to now, only few reports have described this condition from the radiological point of view. Nevertheless, imaging modalities are not burdened by the invasiveness of endoscopic procedures and are also capable in providing useful information about the intestinal tract as well as the surrounding tissues. This is the first case reporting a diffuse involvement of the small bowel and the right colon in a patient suffering of portal hypertension due to cirrhosis evaluated through the performance of computed tomography and magnetic resonance enterography.